A comparison study of bioanalytical methods for detection and characterization of anti-velaglucerase alfa antibodies. (May 2017) - Najarian, Diana R; Hilton, Kelly; McCauley, Thomas; Qiu, Yongchang
Aim: To provide more efficient and timely immunogenicity testing service to support routine patient care, the original complex testing algorithm for evaluation of anti-velaglucerase alfa antibodies has been simplified and individual methods (screen, confirm, titer, neutralizing antibody [NAb] and IgE) have been redeveloped/optimized and validated.Results: To compare the performance of different methods, 50 velaglucerase alfa-treated patient samples were analyzed using both old and new methods for the presence of antidrug antibodies (ADAs) and 31 ADA-positive samples were analyzed for neutralizing capacity. The ADA and NAb statuses are almost identical from both methods and both ADA and NAb titer results are highly correlated with a Spearman's correlation of 0.96 and 0.86, respectively.Conclusion: The original and new testing methods can be considered interchangeable for the measurement of total and neutralizing anti-velaglucerase alfa antibodies.